GGPS1‐associated muscular dystrophy with and without hearing loss. Issue 9 (23rd July 2022) - Kaiyrzhanov, Rauan; Perry, Luke; Rocca, Clarissa; Zaki, Maha S.; Hosny, Heba; Araujo Martins Moreno, Cristiane; Phadke, Rahul; Zaharieva, Irina; Camelo Gontijo, Clara; Beetz, Christian; Pini, Veronica; Movahedinia, Mojtaba; et al.
Abstract: Ultra‐rare biallelic pathogenic variants in geranylgeranyl diphosphate synthase 1 ( GGPS1 ) have recently been associated with muscular dystrophy/hearing loss/ovarian insufficiency syndrome. Here, we describe 11 affected individuals from four unpublished families with ultra‐rare missense variants in GGPS1 and provide follow‐up details from a previously reported family. Our cohort replicated most of the previously described clinical features of GGPS1 deficiency; however, hearing loss was present in only 46% of the individuals. This report consolidates the disease‐causing role of biallelic variants in GGPS1 and demonstrates that hearing loss and ovarian insufficiency might be a variable feature of the GGPS1 ‐associated muscular dystrophy.